A novel twin injector strategy for direct cylinder barrel injection of LPG in a 2S-SI engine. (15th December 2015) - Pradeep, V.; Ramesh, A.
Highlights: Energy saving, low pressure, direct gaseous LPG injection in engine. Significant reduction in HC emissions at all operating conditions. More suitable for improved injector durability. Abstract: A novel strategy of using twin injectors mounted on the cylinder barrel of a two-stroke spark ignition (2S-SI) engine for direct injection of Liquefied petroleum gas (LPG) is developed and compared with manifold injection. Gaseous LPG at a low pressure of about 4–4.5 bar was used and the injectors were located opposite each other and above the transfer ports. Experiments were conducted at the best injection and spark timings at 3000 rpm. Results at 25% and 100% throttle positions over different overall equivalence ratios are presented. The twin direct injection system led to significant reductions in hydrocarbon (HC) emissions of about 80% at both the throttle positions as compared to the manifold injection method due to reduction in short-circuiting losses. The best brake thermal efficiency was also improved from 19.7% to 25.2% at full throttle. Oxides of Nitrogen (NO) emissions were lower and carbon monoxide (CO) levels were higher due to charge non homogeneity. Experiments were also done with a single injector mounted on the cylinder barrel. The twin direct injection system resulted in significantly lower HC emissions and allowed operation under wider range of equivalence ratios with later injection timings as compared to the single injector strategy indicating its superior mixture preparation characteristics.